Who benefits from economic freedom?: Unraveling the effect of economic freedom on subjective well-being - Gehring, Kai (World development, 2013)
Who benefits from economic freedom? Results from a panel of 86 countries over the 1990-2005 period suggest that overall economic freedom has a significant positive effect on subjective well-being. Its dimensions legal security and property rights, sound money, and regulation are in particular strong predictors of higher well-being. The overall positive effect is not affected by socio-demographics; the effects of individual dimensions vary, however. Developing countries profit more from higher economic freedom, in particular from reducing the regulatory burden. Culture moderates the effect: societies that are more tolerant and have a positive attitude toward the market economy profit the most.
Gesehen am 17.03.2021